2007
DOI: 10.1088/0964-1726/16/4/063
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic model for ionic polymer–metal composite sensors

Abstract: A dynamic, physics-based model is presented for ionic polymer-metal composite (IPMC) sensors. The model is an infinite-dimensional transfer function relating the short-circuit sensing current to the applied deformation. It is obtained by deriving the exact solution to the governing partial differential equation (PDE) for the sensing dynamics, where the effect of distributed surface resistance is incorporated. The PDE is solved in the Laplace domain, subject to the condition that the charge density at the bound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
144
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(147 citation statements)
references
References 33 publications
3
144
0
Order By: Relevance
“…The sensor mode has been studied in, e.g., [12][13][14][15][16][17][18][19][20]. The experimental IPMC was implemented as a control system with four distributed inputs and four distributed outputs.…”
Section: Construction Of Sectioned Ipmc and Experimental Systemmentioning
confidence: 99%
“…The sensor mode has been studied in, e.g., [12][13][14][15][16][17][18][19][20]. The experimental IPMC was implemented as a control system with four distributed inputs and four distributed outputs.…”
Section: Construction Of Sectioned Ipmc and Experimental Systemmentioning
confidence: 99%
“…In this paper, we have numerically solved for C 1 (x,t). The solution C 1 can then be integrated to obtain D(x,t) using (4). Under the assumption that the electrolyte has very good ionic conductivity, one gets D(0,t) = 0 and thus D(x,t) is expressed as…”
Section: Full Modelmentioning
confidence: 99%
“…The sensing properties of IPMCs and polyelectrolyte gels have been investigated and described as ion redistribution induced by the mechanical deformation. [1][2][3][4] Some researchers have also studied conjugated polymers' electrical response to mechanical deformation. Takashima et al observed a mechanically induced electrochemical current in a free-standing film of polyaniline (PANI).…”
Section: Introductionmentioning
confidence: 99%
“…Electrode deposition seldom results in the formation of a highly heterogeneous layer, whose conductive and dielectric properties differ from both the polymer and the metal salt [22][23][24][25][26]. Charge redistribution in the vicinity of such regions is considered to be a primary factor in both IPMC actuation [27][28][29][30] and sensing [31][32][33][34]. In [24], we have presented the notion of "composite layer" to describe IPMC charge transport at the ionomer-electrode interface, building on physical insight offered by the concepts of inner electrode [25], intermediate layer [26], and active area model [22,23].…”
Section: Introductionmentioning
confidence: 99%